Enterococcus faecalis antigens in human infections. - Xu, Y (1997)
Genomic libraries of two Enterococcus faecalis strains, OG1RF and TX52 (an isolate from an endocarditis patient), were constructed in cosmid vectors pBeloBAC11 and pLAFRx, and screened with a serum from a rabbit immunized with surface proteins of an E. faecalis endocarditis isolate and sera from four patients with enterococcal endocarditis. Seventy-five cosmid clones reacted with at least two of the sera. Thirty-eight of the 75 immunopositive clones were considered to contain distinct inserts based on their DNA restriction patterns and were chosen for further subcloning into a pBluescript vector. Each sublibrary was screened with one of the five sera, and the DNA sequence of the immunopositive subclones was determined. Analysis of these sequences revealed similarities to a range of proteins, including bacterial virulence factors, transporters, two-component regulators, metabolic enzymes, and membrane or cell surface proteins. Fourteen subclones did not show significant similarity to any sequence in the databases and may contain novel genes. Thirteen of the immunopositive cosmid clones did not yield immunopositive subclones, and one such cosmid clone produced a nonprotein antigen in Escherichia coli.